Cucumeris Mite (Suggested Common Name) Neoseiulus cucumeris (Oudemans) (Arachnida: Mesostigmata: Phytoseiidae) - Garima Kakkar; Vivek Kumar; Cindy McKenzie; Lance S. Osborne (EDIS, 2020)
Includes: Introduction - Synonymy - Distribution - Description and Biology - Host Range - Economic Importance - Selected References.